Maxim of Politeness Used in “The Grand Final of American Got Talent 2021”: A Pragmatics Analysis - Rini; Eko Heriyanto; Ahmad Muhid (English Education Department - Universitas Nasional Karangturi, 2023)
This research entitled Maxim of Politeness Used in “The Grand Final of American Got Talent 2021”: A Pragmatics Analysis. This research focused on Leech’s theory maxim of politeness found in The Grand Final of American Got Talent. The purpose of this research is to identify, classify, analysis the types and the function of politeness in maxim used in the conversation in the event of The Grand Final of American Got Talent. The research method was conducted on qualitative methods. The data source was taken from the event of American Got Talent on youtube. The data are collected by listening method (simak) and note-taking technique (catat). In collecting data, the writer concentrates on the utterance which contains the maxim of politeness produced by the judges and participants of the grand final. Based on the result of the maxim of politeness in The Grand Final of American Got Talent 2021, it was found that six types and functions are maxims of politeness. There are tact maxims, generosity maxims, approbation maxims, modesty maxims, agreement maxims, and sympathy maxims. It is expected that this research will help the students and other readers in learning the pragmatic aspects, especially about the maxim of politeness.